Predictors of Cisatracurium Continuous Infusion Dose in Acute Respiratory Distress Syndrome. (August 2021) - Merkel, Alison; Massey, Kyle; Bellamy, Cassandra; Miano, Todd; Fuchs, Barry; Candeloro, Christina
Neuromuscular blockade (NMB) with cisatracurium may improve outcomes in the acute respiratory distress syndrome (ARDS) population; however, optimal dosing strategy remains unknown. Factors affecting pharmacokinetics and pharmacodynamics of cisatracurium may impact the dose required to achieve adequate train-of-four (TOF) response. The aims of this study were to determine cisatracurium dose requirements in a critically ill ARDS population and to identify clinical factors that affect dosing. This was a single-center, retrospective cohort study of medical intensive care patients who received cisatracurium infusion for treatment of ARDS. "Stable dose" was defined as the infusion rate producing 2 consecutive TOFs of 1/4 to 2/4. Factors examined for association with dose were temperature, pH, age, and the presence of acute kidney injury (AKI). The analysis included 39 patients. The median stable dose of cisatracurium was 2.8 (2.0, 3.1) μg/kg/min. Multivariable linear regression model for weight-normalized dose identified AKI as a factor independently associated with steady-state dose requirements (% change −31.4, 95% confidence interval [CI]: −51.9, −2.3). Our study provides information on cisatracurium doses required in patients with ARDS to reduce time required to reach goal TOF. Further studies are needed to determine effect of AKI on cisatracurium dose requirements and clinical outcomes.